An Overview of Familial Hypocalciuric Hypercalcemia - Huzmeli, Can (Journal of Clinical Nephrology, 2024)
Familial hypocalciuric hypercalcemia (FHH) is one of the rare reasons for hypercalcemia. FHH is an autosomal dominant disease that is inheritable. The most common calcium sensitive receptors (CaSR) develop because of the inactivation of. In addition, they also develop due to the function loss of AP2S1 and GNA11. The FHH sickness is characterized by hypercalcemia, hypocalciuria, the regular or increased level of the parathyroid hormone, and normal renal function. The symptoms of hypercalcemia are usually not observed. It is often diagnosed by calculating the calcium/creatine clearance ratio of a 24-hour urine sample, and then genetically looking at it. FHH is usually a benign disorder, and when symptomatic and rarely complications develop, calcimimetics are used or parathyroidectomy can be performed. In conclusion, FHH is a benign and genetically transmitted, moderate cause of hypercalcemia. It is rare and usually asymptomatic.